Rehabilitasi Psikologis Perempuan Korban Kekerasan Rumah Tangga: Rekonstruksi Hukum Keluarga Islam dalam Konteks Kontemporer - Mufid Arsyad (Bulletin of Counseling and Psychotherapy, 2024)
This research departs from the fundamental problem that the normative construction of Islamic family law still tends to be oriented towards the legal-formal regulation of husband-wife relations and has not adequately positioned the psychological rehabilitation of female victims of domestic violence (KDRT) as an inherent legal need, even though the psychological impact on victims is severe and long-term. This research aims to critically analyze the position of psychological rehabilitation of victims of KDRT in Islamic family law, identify the limitations of the classical fiqh approach and applicable family law regulations, and formulate a reconstruction model of Islamic family law that is oriented towards the psychological recovery of victims in the context of contemporary Muslim society. The theoretical framework used is the concept of mu‘āsyarah bi al-ma‘rūf, maqāṣid al-sharī‘ah, and maṣlaḥah al-Ghazālī, with a normative legal research method enriched with a socio-legal approach; Primary data sources include the Qur'an, hadith, classical and contemporary fiqh literature, and laws and regulations related to domestic violence and Islamic family law, collected through systematic literature studies and analyzed qualitatively and conceptually. The results of the study indicate that psychological rehabilitation of female victims of domestic violence meets the qualifications of maṣlaḥah darūriyyah and therefore can be reconstructed as a normative obligation in Islamic family law, which is implemented through reorientation of religious court practices, strengthening women's rights after violence, and integration of trauma-based recovery services. This study recommends that national policies, particularly in the renewal of Islamic family law, religious court guidelines, and integrated service systems for victims of domestic violence, explicitly integrate psychological rehabilitation as a mandatory part of women's legal protection to ensure sustainable and equitable recovery.